A Review of Microsurgery Versus Endoscopy: Controversies for Treatment of Colloid Cysts - Razzaghi, Alireza; Yousefi, Atefeh; Alizadeh, Sajjad (International Clinical Neuroscience Journal, 2019)
Background: There is controversy about the value of endoscopic methods compared to microsurgical methods in the treatment of challenging colloidal cysts. This study aimed to review the findings of literature which studied microsurgery or neuroendoscopy in the colloid cyst. Methods: An advanced search in PubMed, Science Direct, and Google Scholar databases performed using keywords such as: “microsurgery,” “endoscopy,” “microsurgery versus endoscopy,” and “colloid cysts.” Results: Reviewing the findings of related studies showed some differences in sections of surgical management, microsurgery, endoscopy, complete cyst resection, recurrence rate, length of stay, and complications between the two surgical methods in the treatment of colloid cyst. Conclusion: Despite some disadvantages of endoscopy, it seems this method has more privileges than the other methods.